Structural Contradiction of Economic Growth as a Threat to the Human Capital Reproduction Process in Russia - Solodukha, Petr V.; Vasiutina, Ekaterina S.; Korolkova, Nataliya A.; Erokhin, Sergey G.; Starostenko, Vladimir K.; Matraeva, Liliia V. (International Journal of Economics and Financial Issues, 2016)
The paper reviews the short- and long-term impact of economic growth on the human capital reproduction process. The economic growth is presented as a total of the three constituent parts: structural (potential), cyclical and conjunctural components. Based on the 1999-2013 data, the individual effect of each component of economic growth on qualitative and quantitative indicators of human capital is analyzed. It is shown that to date no conditions for economic growth in Russia through expanded human capital reproduction have been created. Keywords: Economic growth, human capital reproduction, “resource curse”, balance of the national economic system. JEL Classifications: O10, O40, E24